Redefining the Extension Role of State Agricultural Universities to Meet the Emerging Challenges - P. Sethuraman Sivakumar,; B.S. Sontakki,; V.K. Jayaraghavendra Rao, (Journal of Agricultural Extension Management, 2025)
Indian agricultural research and extension systems serve more than 90 million farmers, majority of whom are small and marginal. Several approaches were attempted since independence to streamline the public extension system with a view to make it more efficient in meeting farmer’s needs. These efforts, however, could help the farmers of only a few selected regions by improving their productivity and income, but large chunk of small and marginal farmers with poor access to natural resource base were, unfortunately, left out. One of the important landmarks in these efforts was the establishment of the State Agricultural Universities (SAUs) with the three-pronged mandate of agricultural education, research and front line extension. Although primarily mandated to impart secondary and tertiary level education in agriculture and allied sciences, the SAUs have equally important responsibilities on the agricultural research and extension fronts. A quick retrospective analysis of green revolution vis-a-vis role of extension indicates that, indeed the SA Us could contributed equally by way of their extension efforts to the green revolution. The recent changes in global agricultural scenario have necessitated competitive agricultural environment where cost-effective, productive and sustainable technologies play a crucial role. In this context, the SAUs have to play a pivotal role. In fact, the SAUs are well equipped to provide the much needed on-farm research back up to develop, assess, refine and transfer appropriate agricultural technologies that can trigger the next phase of green revolution